Ecological Studies of Desert Soils of Churu, Rajasthan with Special Reference to Certain Common Plant Species - Sharma, B.M. (Journal of Soil and Water Conservation, 2022)
The soil of a nation is its most valuable heritage. The importance of the study of soils has long been recognized in ecological investigations and as a basis of plant indicators. The ecological studies of desert soils particularly are useful and may prove of help in the operations on the check of the march of desert. Tamhane et al (1959) are of the opinion that a knowledge of the soils of arid and semi arid climates of India is important not only from the point of view of practical agriculture but also from the view of a wider basis of classification of the soils of this group. The importance of soil analysis in understanding the occurrence and distribution of plants and plant communities, is beyond all questions. This paper is, therefore, intended to present the analytical characters of soils of Churu, Rajasthan under certain dominant plant species only. This would fill up the long standing gap about our knowledge of the chemical makeup of the desert soils. The investigation was carried out in 1960-62.